A Multimodal Critical Discourse Analysis on Political Speech by Presidential Candidate for the Republic of Indonesia 2024 - Syah, Saprudin Padlil (SUAR BETANG, 2024)
This research aims to explore the meaning behind the discourse of the political speeches of the 2024 presidential candidates: Anies Baswedan, Ganjar Pranowo, and Prabowo Subianto. This research uses Van Dijk's critical discourse analysis model, Anstey and Bull's semiotic system, and Kress and Leeuwen's visual grammar. Based on the research, it is known that (1) the speeches of Anies, Ganjar, and Prabowo have different themes based on macrostructure analysis; (2) in Anies, Ganjar, and Prabowo's political speeches, they use linguistic tools, both implied and explicit; (3) in their political speeches, Anies, Ganjar, and Prabowo used other semiotic sources in the form of multimodal, namely visual, audio, gesture, and spatial; (4) the speeches of the three candidates showed their knowledge of Indonesia, their opinions and attitudes towards Indonesia, and their ideology in their elections; and (5) the speeches of the three candidates show that they have extensive resources and access to the content of their speeches. AbstrakPenelitian ini bertujuan menggali makna di balik wacana pidato politik bakal calon presiden Republik Indonesia tahun 2024: Anies Baswedan, Ganjar Pranowo, dan Prabowo Subianto. Penelitian ini menggunakan model analisis wacana kritis Van Dijk, sistem semiotik Anstey dan Bull, serta gramatika visual Kress dan Leeuwen. Berdasarkan penelitian diketahui bahwa (1) pidato Anies, Ganjar, dan Prabowo mempunyai tema yang berbeda berdasarkan analisis struktur makro; (2) dalam pidato politik Anies, Ganjar, dan Prabowo menggunakan peranti kebahasaan, baik tersirat maupun tersurat; (3) dalam pidato politiknya, Anies, Ganjar, dan Prabowo menggunakan sumber semiotik lainnya yang berupa multimodal, yaitu visual, audio, gestur, dan spasial; (4) pidato ketiga capres tersebut menunjukkan pengetahuannya tentang Indonesia, opini dan sikapnya terhadap Indonesia, dan ideologinya dalam pencapresan mereka; dan (5) pidato ketiga capres menunjukkan bahwa mereka mempunyai sumber daya dan akses yang luas terhadap isi pidato mereka.